Diversidade genética estimada por meio de marcadores moleculares e morfológicos em acessos de mini-tomate - Preczenhak, Ana Paula (2013)
The tomato is the second most cultivated and consumed vegetables in the world and is among the most genetically studied plant species and phenotypically modified. Tomato production has grown in recent years, and this growth is due to the introduction of new cultivars and varieties such as mini-tomatoes, developed by breeding programs. In prebreeding programs the characterization of accessions of a germoplasm bank is essential to determine the usefulness of the accessions as a source of genes of interest. This paper describes the establishment of mini-tomato UNICENTRO germplasm bank and the characterization of this germplasm bank by means of molecular markers, morphological characters, agronomic performance and fruit color. For molecular analysis was used 11 ISSR (Inter-simple sequence repeat) primers. The polymorphism of ISSR was 88%, considered high for tomato species. Based on the results of the PIC (polymorphism information content), MI (markers index) and RP (resolving power) primers 878, 861, 807, 815 and 836 are the most informative and the most efficient in the discrimination of accessions, therefore the most suitable for studies with mini-tomatoes.. The average similarity between accessions was 64%, accesses RVTC-15 and IAC420-62 were the least similar (13%) and accessions RVTC-25 and RVTC-26 the most similar (96%). The 6 and 8 groups generated in the dendogram (molecular and morphological) showed no relationship with the local of sampling. With morphological data was obtained average standardized distance between access of the 0.60. The access IAC1498-63 was show the higher distance between any access to morphological characteristics. Although it is difficult to make a direct comparison between similarity / divergence, obtained with molecular markers with genetic distance, standardized distances (in values ranging from 0 to 1) made in this work, allows a more direct comparison and therefore conclude that iii the morphological markers, compared to molecular markers, demonstrated greater capacity to differentiate genotypes.. As for agronomic performance, access RVTC-22 is the genotype that most stands out for good fruit production and high soluble solids. However, considering the different criteria for fruit color, accesses IAC1622-64 and IAC392-59 were also important and may indicate these three accessions for breeding programs of mini-tomatoes. Based on these results it can be concluded that the accessions showed good values of divergence molecular and morphoagronomic to all features, so these accessions are potentially useful in breeding programs of minitomatoes.